Adaptive backstepping H∞ tracking control with prescribed performance for internet congestion. (January 2018) - Liu, Yang; Liu, Xiaoping; Jing, Yuanwei; Zhou, Shaowei
Abstract: This paper extends the well-known control method, prescribed performance control (PPC), to network congestion control problems. An adaptive H ∞ tracking problem for Transmission Control Protocol/Active Queue Management (TCP/AQM) system with external disturbance is studied. Firstly, a modified network model is given. And then, the model is changed to an equivalent error model by using error transformation. Next, to solve the network congestion problem, prescribed performance, backstepping technique, adaptive control and H ∞ control are combined to design a congestion controller. Due to the use of prescribed performance, the controller can guarantee both the transient and steady state performance of the system. Meanwhile, the output of the system can track the desired queue, and unknown link capacity can be estimated. Finally, a simulation result is shown to clarify the feasibility and effectiveness of proposed approach. Abstract : Highlights: A new network model is proposed by combining the two existing models. A novel congestion control method is presented to solve a tracking problem by using PPC, adaptive backstepping, and H-infinity control. The steady and transient state performances of the tracking error can satisfy the design requirements. The output of system tracks the desired trajectory with proposed controller. Unknown parameter can be estimated well.